Table of contents, editorial board, and other front matter - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1980)
Editorial front matter and table of contents for vol. 63, no. 4, Oct.-Dec. (1980) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education